Internalisasi Nilai Moderat dalam Beragama Mahasiswa - Zaenul Abidin; Muh. Hambali; Miftahul Huda (Syntax Literate, 2023)
The Hamzanwadi Pancor Islamic Institute is an Islamic university that upholds moderate values in religion, but it is not a necessity that ideas that are not in line with religious moderation can enter campus at any time. So a more serious effort is needed to foster students. The purpose of this study, 1) Knowing the concept of religious moderation, 2) Knowing the process of internalizing moderate values in student religion, 3) Knowing the impact of internalizing moderate values in religious students. This type of research is an empirical research (field search) that uses a qualitative approach. Primary data obtained through the process of interviews, observation, and documentation. The secondary data obtained through literature study, namely by studying books, as well as other supporting literature such as articles and journals related to this research. The results of this study, 1) The concept of religious moderation implemented at IAIH Pancor, namely Islam that is rahmatan lil 'alamin which adheres to the principles held by Ahlussunna Wal Jamaah with a tendency to Wasathiyyah Islamic values. In the sense of an attitude that prioritizes the middle way, it is not textual, and also not liberal in religion. And the moderate attitude built by IAIH Pancor also emphasizes the harmony between religion and the state. 2) The process of internalizing moderate values is carried out through several activities, first. NWDI's education, second. Book study. 3) The impact of internalization of moderate values, First. shapestudents who are inclusive in religion, Second. mform students who love religion, nation, and state.